STUDI LIVING QUR’AN DALAM TRADISI PEMBACAAN SURAT AR-RUM AYAT 21 SEBELUM MELAKUKAN AKAD NIKAH DI KEC. COT GIREK, ACEH UTARA - Binti Yunus, Zulia Rahmi (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2021)
One form of applying the Qur’an in social life is reading one or several certain verses when performing a ritual. Such as reading the letter ar-Rum verse 21 which is usually done before the marriage contract in the district Cot Girek North Aceh. This study uses field research methods through observation and interviews with the aim of observing the phenomenon of the living al-Qur’an that occurs in society. This study came to the conclusion that the tradition of reading the letter ar-Rum verse 21 has long been carried out by the people of Cot Girek until now. Because they believe that reading the Letter ar-Rum verse 21 can bring blessing to the household and as a means of friendship for the two families of the bride and groom.